PENGARUH PENERAPAN PRINSIP GOOD GOVERNANCE TERHADAP PENGELOLAAN DANA DESA DI KECAMATAN PERCUT SEI TUAN - Haris Fahmi Harahap; Junita Putri Rajana Harahap (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2022)
The purpose of this study was to determine the effect of Transparency, Accountability and Participation on Village Fund Management in Percut Sei Tuan District. This type of research is quantitative research. This research was conducted in 18 villages in Percut Sei Tuan District. The population and sample in this study consisted of 90 people, each of which was a village head, village secretary, village finance officer, village staff and one village community from 18 villages studied. The source of data used in this study is primary data obtained using a questionnaire and measured using a Likert scale. While the data analysis method used in this study is the method of multiple linear regression analysis carried out with the help of computer software, namely the Statistical Package for Social Science (SPSS 22). The results in this study indicate that: (1) Transparency partially has no significant effect on Village Fund Management. (2) Accountability partially has a significant effect on Village Fund Management. (3) Partial participation has no significant effect on Village Fund Management. (4) Transparency, Accountability and Participation simultaneously have a significant effect on Village Fund Management.